A Novel Micro-Nano Structure Profile Control Agent: Graphene Oxide Dispersion. (16th November 2014) - Ye, Zhong-Bin; Xu, Yuan; Chen, Hong; Cheng, Chen; Han, Li-Juan; Xiao, Lin
Abstract : Graphite oxide sheet, now referred to as graphene oxide (GO), is the product of chemical exfoliation of graphite and has been known for more than a century. A GO sheet is characterized by two abruptly different length scales; the apparent thickness of the functionalized carbon sheet is approximately 1 nm, but the lateral dimensions can range from a few nanometers to micrometers. In this paper, an improved method for the preparation of graphene oxide within a mild condition is described. We have found that cancelling the high-temperature stage and prolonging the reaction time of mid-temperature can improve the efficiency of oxidation process. We utilized FTIR, XRD, Ultraviolet-visible, TGA, Raman spectrum, and XPS measurements to characterize the successfully synthesized GO. SEM images were employed to reveal the interior microstructure of as-prepared GO dispersion. We also wondrously found that the GO dispersion could be used as profile control agent in the oilfield water-flooding. Flooding experiments showed that the GO dispersion has an ability to adjust water injection profile, reduce permeability ratio, and improve conformance factor. So the GO dispersion would have potential applications in oilfield exploitation.